Malaysia: Knowledge-based (k-based) economy era and the journey ahead / Azeman Abdul Majid, Che'Asniza Osman and Mawarti Asyik Samsudin - Abdul Majid, Azeman; Osman, Che'Asniza; Samsudin, Mawarti Asyik (2004)
Global events are taking place at a rapid pace with far-reaching effects. Anything can happen in a blink-of-an-eye. This rapid change is also blowing across the Asian landscape and forms a new economy and tins economy is based on knowledge. "An education revolution is necessary to produce talented human capital in an increasing global and competitive environment", Datuk Seri Abdullah Ahmad Badawi said [5]. The excerpt describes Malaysia is quite apprehensive in participating the tremendous structural transformation of its economy. The arrival of knowledge-based economy shall entail economic benefits and costs. With this opportunity, Malaysia has embarked from an input-driven growth strategy to knowledge driven. This strategic direction was first announced in Budget 2000. The frontiers of knowledge are boundless. It is a new source of motivating growth of nation and the way of life as it helps in producing wealth for firms and economy. Knowledge is now one of the factors of production that drive the economy besides land, labour, or capital. Deriving from vision 2020, Malaysia has adopted several initiatives and aimed at developing into a K-based economy. The most significance is the establishment of the Multimedia Super Corridor (MSC) in 1996, with the intention to forward the development of high technology and innovation for both domestic and foreign companies and the implementation of several flagships applications. This article explains about K- based economy and within it include the characteristics of k-based economy, the rationale to why Malaysia needs K-based economy, our positioning towards K-based economy, the people involved, the challenges and solutions to lead the k-based economy.